Framing Forest Fires and Environmental Activism: a Storytelling Contest about Human Intervention in Nature - Enric Castelló; Marta Montagut (Communication & Society (Formerly Comunicación y Sociedad), 2019)
This article focuses on the processes of sense-making of forest fires in a Mediterranean context. The authors use a textual approach to compare media framing with activist organizational storytelling. The authors conducted a frame analysis in two major daily newspapers in Catalonia (La Vanguardia and El Periódico de Catalunya) during three summers and compared the results with the stories from four leading activist and volunteering organizations that came out of in-depth interviews with their members, one focus group and published materials. The results identified up to five major mainstream media frames, among which were stories focusing on agricultural risk, climate change and weather conditions; imprudent and negligent attitudes; inappropriate fuel management and woodland conditions; and arson. The natural self-regulatory frame was present as part of the discourse of resilience but almost residual. Some journalism focused on the spectacular nature of the events and their dramatic impact, which led to some degree of mediatization of wildfires. The organizations problematized these frames and discussed about the appropriateness of human intervention to prevent forest fires. The results also revealed that activists observed the issue from a broader complexity, replicating frames on “structural responsibility” instead of “individual responsibility” allocation. The authors point out that if wildfires are to be better understood and dealt with more in-depth knowledge is required of different stakeholders’ approaches to preventing forest fires.